Essential Windows Phone 8 - Wildermuth, Shawn (Addison-Wesley, 2013)
"Shawn has created a guide that is easy to read, up-to-date, and comprehensive-covering the entire application surface area for Windows Phone developers. Enjoy!"-Jeff Wilcox, Senior Software Development Engineer, Microsoft Essential Windows® Phone 8 is the definitive guide to creating powerful mobile apps with Microsoft's dramatically improved Windows Phone 8 platform. Ten-time Microsoft MVP Shawn Wildermuth draws on his extensive experience teaching Windows Phone development, helping you to get started fast and master techniques that lead to truly outstanding solutions. Updated throughout, this edition reflects new APIs and development best practices, ranging from new WinRT APIs to voice integration. It also contains a comprehensive new chapter on developing enterprise solutions for business. After introducing the platform and its key improvements, Shawn dives directly into the essentials. Using realistic code, he illustrates today's best techniques for delivering robust, well-performing apps. You'll build a complete app from start to finish and then deepen your skills with increasingly sophisticated techniques. From planning through delivery, Shawn guides you through the entire lifecycle, helping you make the most of Windows Phone 8's valuable capabilities. Whether you're a Windows developer going mobile or a mobile developer moving to Windows Phone, here are all the skills you'll need.